Integrating Augmented Reality with the RADEC Model to Enhance Elementary Students' Problem-Solving Skills on Climate Change Topics - Yulianti Agustin; Atep Sujana; Kusman Rukmana (International Journal of Educational Qualitative Quantitative Research, 2026)
While the RADEC (Read, Answer, Discuss, Explain, and Create) model effectively structures active learning, its application to abstract environmental phenomena often faces cognitive visualization barriers at the elementary level. This study addresses this gap by pioneering the integration of Augmented Reality (AR) within the RADEC framework, shifting from traditional text-based prompts to immersive 3D ecological simulations. The study aims to investigate the impact of this integrated approach on the problem-solving skills of fourth-grade students regarding climate change topics. Utilizing a quasi-experimental non-equivalent control group design, the research involved 62 students divided into an experimental group (n=30, using AR-assisted RADEC) and a control group (n=32, using conventional methods). Data were collected via observation sheets and validated problem-solving essay tests, and analyzed using paired and independent sample t-tests alongside N-gain scores. The independent sample t-test revealed no statistically significant difference in final posttest scores between the two groups (p = 0.124). Crucially, however, the N-gain analysis demonstrated that the AR-assisted RADEC model achieved a substantially higher and moderately effective improvement rate (58.5%) compared to the conventional method (41.0%), which was less effective. Qualitative observations confirmed that the AR integration successfully lowered cognitive barriers and fostered collaboration during the discussion and explanation phases. This integration contributes a novel, technology-enhanced pedagogical framework that bridges the gap between structured instructional models and abstract science concepts, offering a superior acceleration pathway for fostering elementary students' environmental problem-solving capacities.